2008
DOI: 10.1164/rccm.200701-057oc
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tuberculosis Infection in the United States Population

Abstract: In addition to basic TB control measures, elimination strategies should include targeted evaluation and treatment of individuals in high-prevalence groups, as well as enhanced support for global TB prevention and control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
150
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(158 citation statements)
references
References 16 publications
7
150
1
Order By: Relevance
“…The estimates for LTBI are considerably lower than those reached in our calibration process (25% versus 42% for Brazil and 44% versus 62% for India). The estimate for LTBI in the United States of 7.4% is also higher than the 4.2% LTBI prevalence estimated in [37].…”
Section: Insights From the Calibration Processmentioning
confidence: 55%
See 1 more Smart Citation
“…The estimates for LTBI are considerably lower than those reached in our calibration process (25% versus 42% for Brazil and 44% versus 62% for India). The estimate for LTBI in the United States of 7.4% is also higher than the 4.2% LTBI prevalence estimated in [37].…”
Section: Insights From the Calibration Processmentioning
confidence: 55%
“…r < ds). In a recent large-scale study in the United States, it was found that only 25.5% of individuals with LTBI had been diagnosed and that only 13.2% had been prescribed treatment [37]. Treatment for this symptomless condition is lengthy (usually 6-12 months) and often not finished by those who initiate it.…”
Section: How Much Better Would One Vaccination Policy Be?mentioning
confidence: 99%
“…Applying the methodology used in this study to other populations (11,12) may provide a more complete understanding of the test interpretation and test discordance. Finally, further research is needed to better characterize the most appropriate cutoffs to be used for the risk-stratified interpretation of the IGRAs, to maximize sensitivity and specificity in different risk groups and populations.…”
Section: Discussionmentioning
confidence: 99%
“…A skin test performed with PPD-B is referred to as a "Battey skin test" (BST). The BST has been used as an aid in the differentiation of reactivity to M. tuberculosis from reactivity to NTM in Navy recruit (8,11) and National Health and Nutrition Examination Survey studies (10,12,13). It has also been used in many other smaller epidemiologic studies (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…LTBI screening and treatment serve a dual purpose of preventing reactivation of tuberculosis (reactivation TB) in the individual and protecting public health by preventing the spread of TB in the community. Although 9,421 new TB cases were reported in the US in 2014, an estimated 11 million people in the US are living with LTBI [2,3]. The lifetime risk of reactivation TB in those with LTBI is 10 percent, but identification and treatment of LTBI can reduce the risk of active disease by 60-90 percent [4][5][6].…”
mentioning
confidence: 99%